Evaluation of entomopathogenic nematodes for the management of Phyllophaga bicolor (Coleoptera: Melolonthidae) - MELO-M., ELSA LILIANA; ORTEGA-O., CARLOS ALBERTO; GAIGL, ANDREAS; BELLOTTI, ANTHONY (Revista Colombiana de Entomología, 2010)
Scarab larvae (Coleoptera: Melolonthidae) are important pests in a diversity of crops and climates owing to their damage to the quality and yield of agricultural products. An alternative for their biological control are the entomopathogenic nematodes, generalist parasites and effective control agents in laboratory and field trials. Isolates of introduced and native entomopathogenic nematodes were evaluated against third instar larvae of Phyllophaga bicolor. We determined the infectivity and mortality of isolates of Steinernema (S. riobravis-Sr, S. carpocapsae Strain all-Sc, Steinernema sp.-SNI, S. arenarium-Sa and S. feltiae-Sf1 and Sf2) and Heterorhabditis (H. bacteriophora-Hb1, Hb2 and Hb3) at a concentration of 10,000 IJs/ml at 23C and 70 ± 5% R.H. The evaluation was done on larvae that were one, two and three months old. The most ineffective isolates were those of Heterorhabditis (93.75%-Hb2; 89.58% and 64.58%-Hb1-Hb3), compared to those of Steinernema (10.42%-SIN; 12.50%-Sr; 16.67%-Sa, 22.92%-Sc; 33.34%Sf2; 66.67%-Sf1). The lowest mortalities resulted from Steinernema isolates (0%-Sc and SNI; 2.08%-Sr, 6.25%-Sa; 6.25%-Sf2 and 47.92%-Sf1) while the highest were from Heterorhabditis (52.09%-Hb3; 72.92% and 91.67%-Hb1Hb2). Differences were noted in infection (1 = 65.64%, 2 = 42.50%, 3 = 29.17%) and mortality (1 = 53.33%, 2 and 3 averaged 31.46%), depending on larval maturity, with a noticeable reduction in these variables when approaching the prepupa. The genus Heterorhabditis is the most promising for the white grub management, especially when applied to young larvae.